Giants of Tourism - Butler, Richard W (CABI, 2014)
This first partcontains examples of giants in hospitality.It begins with a unique look at'pre-tourism' times, with Kevin O'Gorman(Chapter1) providing a glimpse into the antecedents of modern tourism. His chapter dispels the notion of tourism as a modern phenomenon and traces evidence of travel for pleasure as far back as 1500BC. Most interestingly, O'Gorman gives details of individual action from over 4000 years ago that developed hospitality regulation and codes of operation.We can't help but wonder how many times we have reinvented the wheel since then. There is then an account of ahistorical giant, Beau Nash,who in the 18th century was an innovator in the provision of resort tourism catering to the fashion whims of society. Inreading John Towner's description of Bath (Chapter2), its development based on 'spa tourism' and its appeal to the wealthy, fashionable and society's elite,one cannot but help but drawp arallels to exclusive destinations of to day that still aim to cater to the same market, only hundreds of years later.